Effect of egg on hemoglobin level of pregnant women - Riona Sanjaya; Yona Desni Sagita; Stevi Kinasih Janet (Universitas Aisyah Pringsewu, 2023)
Iron deficiency anemia is one of the most common disorders, especially during pregnancy. Pregnant women are categorized as having anemia if their hemoglobin level is less than 11gr/dl. The need for iron in pregnant women increases by 25% compared to non-pregnant women. Anemia can be prevented by consuming a balanced nutritious diet with sufficient iron intake to meet the body's needs. One food that is believed to have a high nutritional content is eggs. The aim of the study was to determine the effect of chicken eggs on hemoglobin in pregnant women with anemia in the third trimester. This type of quantitative research, with a pre-experimental research design. Respondents in this study were third-trimester pregnant women who experienced mild to moderate anemia. Bivariate data analysis using the Independent Sample T Test. The results of the analysis obtained p-value = 0.000 (p-value less than 0.05) which means that there is an effect of boiled chicken eggs on the increased level of hemoglobin in third-trimester pregnant women. Suggestions for pregnant women are to continue to eat balanced and varied nutritious foods and consume Fe tablets regularly. Abstrak: Salah satu gangguan yang paling sering terjadi terutama selama masa kehamilan adalah anemia defisiensi besi. Anemia pada kehamilan jika kadar hemoglobin dalam darah kurang dari 11gr/dl. Kebutuhan zat besi pada ibu hamil meningkat 25% dibandingkan ibu tidak hamil. Anemia dapat dicegah dengan mengkonsumsi makanan bergizi seimbang dengan asupan zat besi yang cukup untuk memenuhi kebutuhan tubuh. Telur merupakan salah satu makanan dengan zat gizi tinggi. Tujuan Penelitian Untuk Mengetahui Pengaruh Telur Ayam Terhadap Peningkatan Kadar Haemoglobin Pada Ibu Hamil Anemia Trimester III. Jenis Penelitian ini merupakan penelitian kuantitatif, dengan rancangan pra eksperiment. Responden dalam penelitian ini adalah ibu hamil trimester III yang mengalami anemia ringan hingga sedang. Analisis data bivariat menggunakan Uji Independent Sampel T Test. Hasil analisis didapatkan p-value = 0,000 (p-value kurang dari 0,05) yang berarti ada pengaruh telur ayam rebus terhadap kadar haemoglobin pada ibu hamil. Disarankan bagi ibu hamil agar tetap mengonsumsi makanan yang bergizi seimbang serta beragam, dan rutin mengonsumsi tablet Fe.